Wireless Spinal Cord Stimulator with Bipolar Multi-Channel Electrode Array - Dong, Jiawen (Transactions on Computer Science and Intelligent Systems Research, 2024)
Spinal cord stimulators (SCS) are a method used to treat chronic pain and are widely used in the field of modern neuroregulation. Based on the existing literature, this paper compares and discusses the principle and structure of a new wireless spinal cord stimulator with a small range of precise stimulation and the choice of working plan. In this spinal cord stimulator, a bipolar structure combined with multi-channel electrodes is considered, and a passive resonator is used to improve the efficiency of wireless energy transmission. The literature search and research show that the combination of bipolar structure and multi-channel electrode array can produce more concentrated stimulation areas, reduce the stimulation of non-target areas, and thus reduce side effects. In the selection of electrode materials and external equipment, this paper mainly considers the biocompatibility, considering the use of carbon nanotube (CNT) composite materials for the internal electrode materials, at the same time, this paper also considers the impact of voltage overshoot on the electronic equipment, and considers the work plan and material selection to reduce the impact.